The Mycenaean cemetery at Clauss, near Patras : the people, their material remains and culture in context - Paschalidis, Constantinos (Archaeopress Publishing Ltd, 2018)
This title presents the study of the finds from the Mycenaean cemetery of Clauss near Patras, carried out between 1988-1992 under the direction of Prof Thanassis Papadopoulos. During the excavation project, fifteen chamber tombs were located and researched in detail, to be added to those already known from the pre-war excavations by Nikolaos Kyparissis.